Efektivitas Layanan E-Samsat dalam Meningkatkan Kepatuhan Pembayaran Pajak Kendaraan Bermotor di Kota Binjai - Zemila Dearni; Yunita Sari Rioni (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the effectiveness of the E-Samsat service in improving compliance with Motor Vehicle Tax (PKB) payments in Binjai City. The method used is descriptive qualitative with observation, in-depth interviews, and documentation techniques. This study involved 5 taxpayer informants who had different E-Samsat usage intensities (always, routinely, ever, rarely, never) and 1 key informant from the UPT Samsat. The results show that the E-Samsat service through the SIGNAL application and E-Samsat Sumut Bermartabat provide convenience, speed, and transaction security that have a positive impact on PKB payment compliance. This application makes it easier for taxpayers to make payments without having to visit the Samsat office, which of course increases convenience and time efficiency. However, there are still obstacles related to digital literacy and limited network infrastructure that hinder optimal utilization of the service. Many taxpayers do not fully understand how to use the application or do not have adequate access to use the service. Data on the realization of PKB in Binjai City shows an increasing trend in tax revenue after the introduction of the E-Samsat service, although this increase does not fully reflect an optimal level of compliance. This indicates that further public education is still needed regarding the importance of paying taxes and how to use the E-Samsat service. Ongoing supervision is also crucial to ensure that taxpayers not only conduct transactions but also fully understand their obligations. Furthermore, this study's findings suggest that public understanding of the importance of paying taxes still needs to be improved. A more effective communication strategy is needed to ensure that information about E-Samsat and its benefits is more widely disseminated. Overall, while E-Samsat has a positive impact on PKB payment compliance, infrastructure support, digital literacy, and more intensive education and supervision are essential to achieve maximum compliance.